2005
DOI: 10.1590/s0102-33062005000300025
|View full text |Cite
|
Sign up to set email alerts
|

Sporocarpic species of arbuscular mycorrhizal fungi (Glomeromycota), with a new report from Brazil

Abstract: RESUMO -(Espécies esporocárpicas de fungos micorrízicos arbusculares (Glomeromycota), com uma nova ocorrência para o Brasil). Os fungos micorrízicos arbusculares (FMA) são amplamente distribuídos nos ecossistemas terrestres; entretanto, espécies esporocárpicas são pouco documentadas em investigações sobre FMA. Cinco dessas espécies foram encontradas em remanescentes de Floresta Atlântica e em áreas cultivadas, no nordeste do Brasil: Glomus glomerulatum, G. sinuosum, G. coremioides, G. fuegianum e G. taiwanensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
(10 reference statements)
0
3
0
1
Order By: Relevance
“…According to Hawksworth and Rossman (1997), Hawksworth (2001), and Blackwell (2011), tropical forests are such regions, and the exploration of tropical forests have resulted in the discovery of many sporocarpic fungi (Sulzbacher et al 2016(Sulzbacher et al , 2017. These include the recently newly described species of the Glomeromycota from Brazil and Cuba (Torre-Arias et al 2017), AMF species found in these countries, but previously rarely recorded in the world (Goto and Maia 2005), as well as the new Brazilian fungus, S. amazonicum, characterized in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hawksworth and Rossman (1997), Hawksworth (2001), and Blackwell (2011), tropical forests are such regions, and the exploration of tropical forests have resulted in the discovery of many sporocarpic fungi (Sulzbacher et al 2016(Sulzbacher et al , 2017. These include the recently newly described species of the Glomeromycota from Brazil and Cuba (Torre-Arias et al 2017), AMF species found in these countries, but previously rarely recorded in the world (Goto and Maia 2005), as well as the new Brazilian fungus, S. amazonicum, characterized in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The fi rst records of AMF were from agricultural ecosystems (Maia & Trufem 1990) and since then, other investigations in cultivated areas (Weber et al 2004), impacted areas (Silva et al 2005;Mergulhão et al 2009), native areas with "caatinga" vegetation and in fragments of Atlantic Forest (Goto & Maia 2005) have been done, increasing our knowledge of AMF diversity in the region (Maia et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1(3, 4)). The term "sporocarp" is used rather loosely in relation to glomeromycotan fungi, and may be used either in a welldefined manner in which the structures containing spores are enclosed in an evidently differentiated hyphal peridium with further differentiated glebal hyphae, or merely to describe a dense, undifferentiated cluster of spores (e.g., Schenck and Perez, 1990;Goto and Maia, 2005). Since we cannot determine whether the hyphal envelope in the fossils described here represents a peridium sensu stricto, we use the term "sporocarp" in the broadest sense for these fossils.…”
Section: Sporocarp Producermentioning
confidence: 99%